2018
DOI: 10.1002/cbic.201800556
|View full text |Cite
|
Sign up to set email alerts
|

An Engineered Alcohol Oxidase for the Oxidation of Primary Alcohols

Abstract: Structure‐guided directed evolution of choline oxidase has been carried out by using the oxidation of hexan‐1‐ol to hexanal as the target reaction. A six‐amino‐acid variant was identified with a 20‐fold increased kcat compared to that of the wild‐type enzyme. This variant enabled the oxidation of 10 mm hexanol to hexanal in less than 24 h with 100 % conversion. Furthermore, this variant showed a marked increase in thermostability with a corresponding increase in Tm of 20 °C. Improved solvent tolerance was demo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
66
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 65 publications
(67 citation statements)
references
References 37 publications
0
66
0
1
Order By: Relevance
“…Another recent demonstration of the biocatalytic potential of a flavoprotein alcohol oxidase was recently reported by Turner and co‐workers. They showed that choline oxidase can be engineered towards a wider substrate acceptance, for the selective oxidation of primary alcohols to aldehydes …”
Section: Results Of Aox*‐catalyzed Conversions Of Diols and Other Alcmentioning
confidence: 99%
“…Another recent demonstration of the biocatalytic potential of a flavoprotein alcohol oxidase was recently reported by Turner and co‐workers. They showed that choline oxidase can be engineered towards a wider substrate acceptance, for the selective oxidation of primary alcohols to aldehydes …”
Section: Results Of Aox*‐catalyzed Conversions Of Diols and Other Alcmentioning
confidence: 99%
“…16,17,19 Increased use of alcohol oxidases is advantageous as the selective generation of aldehyde intermediates from alcohols has wide applications in the fine chemical industry and as part of biosynthetic cascades. 19,28 MAOs have been broadly exploited for the resolution and functionalization of amines but can be limited by substrate and product inhibition. 29,30 Immobilisation of these enzymes could overcome these limitations.…”
Section: Figurementioning
confidence: 99%
“…Particularly attractive oxidase biocatalysts for immobilisation are galactose oxidase (GOase), choline oxidase and monoamine oxidase from Aspergillus niger (MAO-N), as all have demonstrated broad applications in biocatalysis. [13][14][15] Previous engineering efforts for GOase and choline oxidase have developed a number of variants capable of oxidising a myriad of alcohols and have been demonstrated in both batch and flow reactor configurations, 1,[16][17][18][19][20] including the implementation of GOase in the gram scale biocatalytic manufacture of the investigational anti-HIV drug Islatravir. 21 Additionally, MAO-N versatility has been extensively shown in amine resolution and functionalization.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Particularly attractive oxidase biocatalysts for immobilisation are galactose oxidase (GOase), choline oxidase and monoamine oxidase from Aspergillus niger (MAO-N), as all have demonstrated broad applications in biocatalysis. [13][14][15] Previous engineering efforts for GOase and choline oxidase have developed a number of variants capable of oxidising a myriad of alcohols and have been demonstrated in both batch and ow reactor congurations, 1,[16][17][18][19][20] including the implementation of GOase in the gram scale biocatalytic manufacture of the investigational anti-HIV drug Islatravir. 21 Additionally, MAO-N versatility has been extensively shown in amine resolution and functionalization.…”
mentioning
confidence: 99%